Subgrade Geotechnical Study for Riverbank Road Construction and Maintenance Management System Quality Control - Salem, Zahraa Amad; Ibraheem, Asma Thamir (Al-Nahrain Journal for Engineering Sciences, 2024)
Quality control of riverbank roads is a vital part of the road construction and maintenance process and aims to ensure infrastructure quality, safety, and sustainability. This requires adherence to technical standards, constant auditing, and regular maintenance to maintain the condition of the roads and avoid potential problems. The first step in the quality control of roads is to test the efficiency of the subgrade soil. A geotechnical investigation of subgrade soil under river bank roads is carried out to evaluate the engineering properties of the soil and determine the soil’s ability to bear the loads resulting from vehicle movement and road traffic. This investigation includes analyzing soil samples and laboratory tests to determine soil properties and determine any improvements the soil needs to bear the loads. Soil samples were collected from Al-Kadhimiya Corniche Street. It was dried and subjected to laboratory tests, the soil in this study is classified as poorly graded sand (SP), GS 2.589, the shear strength parameters an internal friction angle of 33 degrees and cohesion of 0.5 kN/m2, and the results of the compaction test indicated that the optimal moisture content was 8.1%, with a maximum dry density was 18.24 kN/m3, CBR 26.04%, and chemical tests (SO3 0.222, pH 8.55, T.SS 0.891, CL 0.085). Software FAARFIELD was used to check pavement design, the thickness design was executed utilising a subgrade CBR value of 26.04%. The subgrade pavement thickness was determined to be 304mm in total. The results agree with the actual design of Al-Kadhimiya Corniche Street, which was recently maintained during the field investigation in 2023.